Probing the heart of an active galactic nucleus: NGC 1068 - Tecza, M; Thatte, N; Maiolino, R (2001)
We present results from integral field spectroscopy of the narrow line region of NGC 1068, carried out with the MPE 3D near infrared imaging spectrometer. A map and velocity field of the [Fe II] fine structure line at 1.64mum is presented. The kinematics of the [Fe II] emission, which arises in partially ionized zones, shows red shifted emission in the north eastern cone of the NLR, and blue shifted emission in the south west, reversed relative to high ionization species such as [Si VI] or [0 111]. We propose a model geometry of the narrow line region which is consistent with existing data and explains the observed [Fe II] kinematics.